Maternal and perinatal outcome in preterm premature rupture of membranes - R., Sudha; Biradar, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preterm premature rupture of membranes (PPROM) and preterm birth results in one third of perinatal mortality and maternal morbidity such as chorioamnionitis and abruption placenta and preterm caesarean section, Preterm premature rupture of membranes occurs in 3% of pregnancies. PPROM is associated with intrauterine infection. Early detection of intrauterine infection may help in prevent neonatal sepsis. Objective of present study was to analyse the maternal and perinatal outcome of PPROM patients between 28 to 36 weeks +6 days and predict intrauterine infection by access the level of C reactive protein to prevent chorioamnionitis and neonatal infection. Methods: A descriptive study was conducted on 126 antenatal patients between 24 to 36 weeks+6 days with PPROM admitted to Department of Obstetrics and Gynaecology, Cheluvamba Hospital Mysore medical college, Mysore, Karnataka, India from February 2022 to July 2022. After establishing the diagnosis of PPROM patients were monitored and maternal and perinatal outcomes were studied. Results: 24% patients had late PPROM. 63% of early PPROM latency period >24 hours and were managed conservatively till 34 weeks. 18% had chorioamnionitis in that 12% CRP positive status and immediate termination of pregnancy. 73% of newborns in this group needed admission due to complications of prematurity like RDS (54.54%). Perinatal mortality (2.12%) was due to sepsis. 80% of late PPROM had latency period 24 hours and sepsis was 36% in >24 hours and 10% in <24 hours. Conclusions: The most common cause of perinatal mortality in early PPROM is prematurity and its complications. Hence conservative management to prolong pregnancy is recommended under strict monitoring for evidence of chorioamnionitis. C-reactive protein helps to pick up chorioamnionitis early. At the earliest evidence of chorioamnionitis termination irrespective of gestational age is warranted. In late PPROM, perinatal outcome is good. So, termination is advised as conservative management shall add to the fetal and maternal morbidity due to sepsis.